Risk group stratification to predict recurrence after transurethral resection in Japanese patients with stage Ta and T1 bladder tumours: validation study on the European Association of Urology guidelines - Sakano, Shigeru; Matsuyama, Hideyasu; Takai, Kimio; Yoshihiro, Satoru; Kamiryo, Yoriaki; Shirataki, Satoshi; Kaneda, Yoshitaka; Hashimoto, Osamu; Joko, Keiji; Suga, Akinobu; Yamamoto, Mitsutaka; Hayashida, Shigeaki; et al. (BJU international, 2011)
Study Type – Therapy (case series)  Level of Evidence 4 What’s known on the subject? and What does the study add? EAU guidelines on non‐muscle‐invasive bladder tumours have been widely used for the prediction of recurrence after TUR. However, there are substantial differences in bladder cancer incidence and mortality rates between European countries and Japan. This study provides useful factors for predicting recurrence and validation of EAU guidelines on the risk group stratification to predict recurrence in Japanese patients with stage Ta and T1 bladder tumours. OBJECTIVE • To validate the European Association of Urology (EAU) guidelines on risk group stratification to predict recurrence in Japanese patients with stage Ta and T1 bladder tumours. PATIENTS AND METHODS • A cohort of 592 Japanese patients who were treated with transurethral resection (TUR) and histopathologically diagnosed with Ta and T1 urothelial carcinoma of the bladder were enrolled in this retrospective study. • The primary endpoint of the present study was recurrence‐free survival, and the median follow‐up duration was 37 months in recurrence‐free survivors. RESULTS • Multivariate Cox proportional hazards regression analysis showed that the Eastern Cooperative Oncology Group performance status (ECOG PS), prior recurrence rate, number of tumours and T category were independent predictors of time to recurrence (P < 0.05). According to the EAU guidelines for predicting recurrence, the vast majority of Japanese patients were classified into intermediate risk. • The intermediate‐risk patients were further divided into intermediate‐low‐risk and intermediate‐high‐risk subgroups based on the European Organization for Research and Treatment of Cancer risk table, and a significant difference in the recurrence‐free survival rates was found between these subgroups (P < 0.001). • It was also found that patients with high risk combined with intermediate‐high risk had significantly poorer recurrence‐free survival rates than those with low risk combined with intermediate‐low risk (P < 0.001). CONCLUSIONS • This is the first report on the ECOG PS as a potentially useful predictor for bladder tumour recurrence. • The risk group stratification of the EAU guidelines for recurrence might not be applicable to Japanese patients with Ta and T1 bladder tumours, but the subgroup classification of intermediate risk could be appropriate.